Pengaruh Atmosphere Toko, Kualitas Produk Dan Lokasi Coffee Terhadap Keputusan Pembelian Di Toko Kopi Rasa Padang - Yudha Putra Dwiyessa; Yesi Elsandra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The purpose of this research is to determine and analyze the influence of Store Atmosphere, Product Quality, and Location of Kopi Rasa Padang coffee shop. The population of this study is consumers of Kopi Rasa Padang, whose exact number is not known. The sample in this study consists of 96 consumers of Kopi Rasa Padang. This research was conducted using a purposive sampling method, which is the selection of samples based on specific characteristics and criteria. The data for this study was obtained from questionnaires distributed directly to respondents. The analysis method used is a quantitative method using IBM SPSS Statistics 22. The results of the study show that Store Atmosphere has a positive and significant effect on Purchase Decision; Product Quality has a positive and significant effect on Purchase Decision; Location has an influence that is not significant on Purchase Decision.